2015
DOI: 10.1097/mcg.0000000000000295
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Refractory Gastrointestinal Strictures With Mitomycin C

Abstract: Local mitomycin C application seems to be a safe and effective therapy for benign refractory GI strictures of varying etiology in both pediatric and adult populations. Although the results of this systematic review are highly encouraging, it should be considered investigational. Additional randomized trials and larger prospective studies are needed to confirm these results and to better define the optimal dose, concentration, duration and technique of mitomycin C application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…The majority of the publications (17 studies) enrolled only pediatric patients, corresponding to 70% of them. The most common etiology was caustic injury, with just 18% of the patients with anastomotic stricture and only 2 adult patients with radiation stricture [ 14 ]. Overall, 94% of 117 patients (pediatric and adults) included had a good response.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the publications (17 studies) enrolled only pediatric patients, corresponding to 70% of them. The most common etiology was caustic injury, with just 18% of the patients with anastomotic stricture and only 2 adult patients with radiation stricture [ 14 ]. Overall, 94% of 117 patients (pediatric and adults) included had a good response.…”
Section: Discussionmentioning
confidence: 99%
“…30 A systematic review of Mitomycin C use in adults and children reported a complete response to therapy in 73% and a partial response in 21% though these uncontrolled data must be interpreted with considerable caution. 31 Other drugs There is the potential for multiple other drug applications to inhibit fibrosis but none have been evaluated in oesophageal stricturing. The process of fibrosis is complex but increasingly well understood.…”
Section: Steroid Injectionmentioning
confidence: 99%
“…The number of MMC applications varied between 1 and 12 with a mean of 2 and 2.6 in pediatric and adult patients, respectively, although the majority [67 children (79%) and 24 adults (63%)] required only 1 to 2 applications. When MMC was applied more than once, intervals ranged from 1 week to 13 months, with a median of 4 weeks (84). To date, no study compares the effectiveness of different concentrations and dosages of MMC; the concentration of 0.4 mg/mL is the most commonly used and appears to be effective.…”
Section: Treatmentmentioning
confidence: 99%
“…Most data on MMC efficacy in treating persistent esophageal stricture are coming from studies involving patients with caustic esophageal injury (79, 84). …”
Section: Treatmentmentioning
confidence: 99%